Gambaran Stres Psikososial dan Faktor-Faktor yang Mempengaruhinya Pada Remaja - Nurul Intan Rendra Zola; Fathra Annis Nauli; Gamya Tri Utami (Poltekkes Kemenkes Jakarta III, 2021)
Teenagers are a transition from children to adults who have a lot of changes,it causes teens to experience psychological stress. The factors that influence psychosocial stress are living conditions, school environment, family economic status, relationships with others, unplanned events and habits. This study aim to determine the description of psychosocial stress and the factors that influence it in students at SMAN 8 Pekanbaru. The total respondents were 101 respondents using accidental sampling.. The measuring instrument used was a questionnaire from Holmes and Rahe and analyzed using univariate.. The results showed that the majority of respondents experienced moderate psychosocial stress (47.5%). Respondents who experienced the condition of the living environment factors were 51.5%, the state of the school environmental factors were 50.5%, family economic status factors were 37.6%, relationship factors with other people were 49.5%, unplanned incidence factors were as many as 31,7% and habit 2,% showed psychosocial stress. The researcher concluded that the majority of respondents experienced moderate psychosocial stress with the most influencing factor is the state of the environment in which they live. This research recommends adolescents to add information and add insight about psychosocial stress and the factors that influence it and can prevent it.